The Influence of Air Cleaners on Indoor Particulate Matter Concentrations and Oxidative Potential in Residential Households in Beijing - Zhan, Ying (My University, 2018)
In many developing regions where poor air quality is endemic, there is a rapidly growing number of air filtration devices available to clean indoor air. However, few studies have been performed to assess their effectiveness. This thesis studies the effectiveness of air cleaner at removing indoor air pollutants including PM2.5 and its components, as well as ozone (O3) and nitrogen dioxide (NO2); the effectiveness in reducing oxidative potential, which is expressed by reactive oxygen species (ROS) activity, is investigated as well. Filter-based PM2.5, O3, and NO2 samples were collected for outdoor, indoor, and personal exposure during the summer of 2016 in Beijing. This study shows that air cleaners can provide a healthier indoor environment, but they do not reduce personal exposure to particles and gas phase air pollutants nor work at reducing personal exposure the oxidative potential of fine particulate matter. Therefore, it is not entirely clear whether air cleaners will provide health benefit to users, and future research should focus on quantifying high pollutant exposure microenvironments to reduce the personal exposure. This thesis will start with the introduction to air pollutions; next, it will be results and discussion on the changes of PM2.5, its component and the oxidative potential of PM with air cleaner installation; finally, it is the conclusion and implication of this study. Followed by the appendix for analysis methods of ozone and nitrogen dioxide as well as the result. Chapter 1 will give an introduction of ambient and indoor air pollution, including air pollution sources, main air pollutants, and their health effects. Then, there will be a review on indoor air pollution control strategies and previous studies on air cleaners. The final part is a statement describing the purpose of this research. Chapter 2 is the results and discussion of the effectiveness of air cleaners at reducing PM2.5 and its components as well as the oxidative potential of PM2.5. This chapter will start with indoor to outdoor correlations, and the indoor to outdoor ratio (I/O) is used to assess the effectiveness of air cleaners. Then, there is personal exposure to the outdoor ratio (P/O), and the microenvironmental method is adopted to evaluate personal exposure. At the end of this chapter, ROS activity results for indoor, outdoor, and personal exposure are analyzed and discussed. Chapter 3 is the conclusion of this thesis. It will summarize the results from this study and point out its limitations. It will also state the significance and implications of this research, ending with future research directions. Appendix will talk about the ozone and nitrogen dioxide chemical analysis methods developed at Water Science and Engineering Lab at UW Madison. They are obtained by using Ogawa O3/NOx passive sampler, and are used employed to assess the O3 and NO2 levels at different environments. The results will be presented and briefly discussed. The method is set up for the study but the data from the pilot study was not sufficient for a chapter discussion but these methods can be used in future studies.